'AP-4', a Medium Maturity, Large Seeded Peanut Variety with Resistance to Tomato Spotted Wilt - Barry L. Tillman; Daniel W. Gorbet (EDIS)
SS-AGR-324, a 3-page illustrated fact sheet by Barry L. Tillman and Daniel W. Gorbet, describes this peanut variety was released by UF/IFAS in 2007 based on its competitive pod yield and excellent seed grade — total sound mature kernel percentage (TSMK), providing the results of tests in three locations over three years. Published by the UF Department of Agronomy, August 2009.